Ideas suicidas y su relación con el comportamiento social en adolescentes del colegio Nacional Adolfo Valarezo de Loja - Mora Quezada, Mary Luisa (2014)
Suicide is a serious public health problem; it has growing very much, in recently years, specially in teens and young adults al globally Through this quantitative, descriptive, correlational and cross-senctional work, the main objectives were to identify the psychosocial factors which have involved in teen decision to kill themselves, and so end with their lifes; to determine the sociodemographic behavior of teens with suicidal ideas, and to establish the relationship between suicidal ideation and social teens behavior and finally develop and spread informative materials related to this theme and to prevent; the following results have gotten. That total sample were 283 students who have applied the test IRSA and CCA, 223 satisfy the inclusion criteria, of which the majority has suicidal ideas in this predominantly male students, whose age is between 16 to 18 years, the main precipitating factors have students with suicidal to cause this problem are: loss of a close relative or friends, also they have had a discussion with someone special recently. In the social behavior that showed the students prevail the suicidal behavior caused by withdrawal and anxiety, by isolation, Getting a results around 10:4 and 10:3 ratios respectively. KEYWORDS • SUICIDE • SUICIDE IDEAS • BEHAVIOR • TEENS